Effects of vitamin D supplementation on the regulation of blood lipid levels in prediabetic subjects: A meta-analysis - Yang, Yixue; Yan, Shoumeng; Yao, Nan; Guo, Yinpei; Wang, Han; Sun, Mengzi; Hu, Wenyu; Li, Xiaotong; Wang, Ling; Li, Bo (Frontiers in Nutrition, 2023)
This meta-analysis aimed to systematically investigate whether vitamin D supplementation reduces blood lipids - total cholesterol (TC), LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C) and triglycerides (TG) - levels in prediabetic individuals. Pubmed, Web of Science, Cochrane Library, Embase, CNKI and WANFANG databases were searched for studies published before February 13th, 2022 (including February 13th, 2022). Five articles were included. The results showed that vitamin D intervention led to significant reduction in TG compared with control or placebo treatment (-0.42[-0.59,-0.25], P<0.001). Subgroup analyses showed that this effect was particularly significant among the studies which included obese subjects (-0.46[-0.65,-0.28], P<0.001), the studies which included also men (not only women) (-0.56[-0.78,-0.34], P<0.001), and the studies with duration of intervention longer than 1 year (-0.46[-0.65,-0.28], P<0.001). Both relatively low dose of 2857 IU/day (-0.65[-0.92,-0.38], P<0.001) and relatively high dose of 8571 IU/day (-0.28[-0.54,-0.02], P=0.04) of vitamin D supplementation led to reductions in TG, and the effect was observed both in the Northern Europe (-0.65[-0.92,-0.38], P<0.001) and in the Asian (-0.25[-0.48,-0.03], P=0.03) countries subgroups. No significant effects on TC, HDL-C and LDL-C were shown. In conclusion, vitamin D supplementation might beneficially affect TG levels in individuals with prediabetes. Particularly longer duration of treatment, more than 1 year, with doses which correct vitamin deficiency/insufficiency, can have beneficial effect. This meta-analysis was registered at www.crd.york.ac.uk/prospero (CRD42020160780).